Metastatic Merkel Cell Carcinoma Masquerading as Multiple Immune-Related Adverse Events - Farees Saqlain; Sophia Z. Shalhout; Kevin S. Emerick; Tomas G. Neilan; Tatyana Sharova; David Michael Miller (Case Reports in Dermatological Medicine)
Merkel cell carcinoma is a rare cutaneous neuroendocrine carcinoma with a high rate of regional and distant metastasis and mortality. Here, we report a novel case of Merkel cell carcinoma which presented as a primary lesion to the left cheek with regional lymph node involvement and was treated with pembrolizumab and radiation. Widely metastatic disease eventually revealed on autopsy clinically mimicked immune-related organ insult leading to management with immunosuppressants. The patient also had a biopsy-confirmed immune-related cutaneous adverse event during admission. The case highlights a rare circumstance in which disease progression masqueraded as multiple immune-related end-organ adverse events. Contribution of on-target anti-PD-1 toxicity remains a possibility.